IMPLEMENTASI MODEL CIPP (CONTEXT, INPUT, PROCESS, AND PRODUCT) DALAM EVALUASI PROGRAM BILINGUAL SCHOOL DI SMA SWASTA KRISTEN BNKP GUNUNGSITOLI - Mendofa, Wendi Alsenal; Setiwati, Esti (Jurnal Sosialita, 2026)
This study aims to assess the implementation of the bilingual program carried out at SMA Swasta Kristen BNKP Gunungsitoli by utilizing the CIPP (Context, Input, Process, Product) evaluation model introduced by Stufflebeam. The selection of this model is based on its ability to provide a comprehensive assessment of an educational program. The research was conducted using a descriptive qualitative approach and employed a case study method. Data were collected through interviews, observations, and document analysis, involving the principal, teachers, and students as key informants. The findings indicate that in terms of context, the bilingual program emerged as a response to globalization demands and the school’s vision to produce graduates with international competitiveness, supported by international collaborations in the form of student exchange programs and scholarship opportunities for underprivileged but high-achieving students. Regarding input, the availability of resources was deemed adequate, although challenges remain in terms of teacher quality and supporting facilities. The implementation process has not been consistently optimal, mainly due to language-related difficulties experienced by some teachers. Meanwhile, in the product aspect, there has been an improvement in students' English proficiency, although the outcomes have not yet fully met the expected targets. Based on these findings, it is recommended that the school strengthen its internal policies, enhance teacher capacity through training, and provide more appropriate learning materials to ensure the sustainability and effectiveness of the bilingual program.